Multifaceted approached in gerating and recovering requirement traceability - Siti Rochimah, Siti Rochimah; Wan Kadir, Wan W. N.; Abdullah, Abdul H. (Penerbit UTM Press, 2007)
Software evolution is inevitable. When a system evolves, there are certain relationships among software artifacts that must be maintained. Software must be continually changed to remain satisfactory in use. Requirement traceability is one of importance factor in facilitating software evolution since it maintains the artifacts relationship before and after a change is perfonned. This position paper aims at hypothesizing that utilizing a multifaceted approach to traceability generation and recovery can provide significant support for facilitating software evolution process. The multifaceted traceability approach contains three main facets that compose the whole traceability approach. Facet-l is a syntactical similarity matching process, Facet-2 is a link prioritization process, and Facet-3 is a heuristic-based process. Those three facets works in an integrated mode to construct traceability links among artifacts and are run on top of a particular ready-to-use integrated environment development (IDE) in order to facilitate the traceability generation and recovery as well as to ease the artifacts maintenance.